Love Relationship Satisfaction, Love Styles and Suicidal Ideation Among University Students - Ng, Yi Xian; Lee, Jun Choi; Ahmad Sofian, Shminan (Unimas Publisher, 2023)
The suicide rate is increasing at an alarming pace, even among university students. Thus, this study attempted to identify suicidal ideation among university students through the perspective of love relationships (love satisfaction, love styles) and gender differences. This quantitative study presents and discusses empirical findings from a survey of 873 Malaysian public university students conducted by questionnaire. Analysis of the responses demonstrated that love relationship satisfaction was not associated with suicidal ideation among university students. On the other hand, there is a link between university students' love styles and suicide ideation. Love relationship satisfaction is positively correlated with love styles as well. The prevalence of suicidal ideation among university students varies significantly by gender, with females being more likely than males to harbour such thoughts. Therefore, establishing a crisis intervention programme and providing professional psychological and counselling services would assist, help, and support university students to reduce the emergence of suicide ideation related to this matter.